2019
DOI: 10.1002/14651858.cd009768.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells as treatment or prophylaxis for acute or chronic graft-versus-host disease in haematopoietic stem cell transplant (HSCT) recipients with a haematological condition

Abstract: Mesenchymal stromal cells as treatment or prophylaxis for acute or chronic graft-versus-host disease in haematopoietic stem cell transplant (HSCT) recipients with a haematological condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 68 publications
2
67
2
3
Order By: Relevance
“…Our meta-analysis indicates that the prophylactic administration of allogeneic MSC to patients undergoing HSCT increases the probability of survival, partly because MSC prevent the occurrence of GvHD. A recent meta-analysis [33] including five randomized controlled trials (RCTs) showed no significant differences for allcause mortality between MSC and no MSC groups, in contrast to our results. We believed that these different results could be due to the lower number of cases and shorter end point of this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our meta-analysis indicates that the prophylactic administration of allogeneic MSC to patients undergoing HSCT increases the probability of survival, partly because MSC prevent the occurrence of GvHD. A recent meta-analysis [33] including five randomized controlled trials (RCTs) showed no significant differences for allcause mortality between MSC and no MSC groups, in contrast to our results. We believed that these different results could be due to the lower number of cases and shorter end point of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The characteristics of the 35 studies reporting data for the treatment of aGvHD and/or cGvHD are summarized in Table S3 (see Additional file, pp. [33][34][35][36]. Only six of these studies reported data of interest for control patients (aGvHD, n = 182 patients; cGvHD, n = 14 patients; Table S4, pp.…”
Section: Mesenchymal Stromal Cells For the Treatment Of Steroidrefracmentioning
confidence: 99%
“…A number of studies have assessed the safety and efficacy of cell therapies in adults with GVHD, as described in the recent meta-analysis [39]. A number of factors are relevant to the experience reported in adults with aGVHD treated with MSCs, including variations in the type of design (prophylaxis versus treatment of GVHD), type of MSCs (adipose tissue, cord blood, or bone marrow derived cells), specific trial design elements (first line in new-onset GVHD, concomitant corticosteroids and MSCs after GVHD diagnosis, or established steroid refractory), choice of primary efficacy endpoint (the currently established day 28 overall response or durable complete response), choice or comparator, and specific aGVHD patient attributes such as severity of disease and organ involvement.…”
Section: Discussionmentioning
confidence: 99%
“…В дополнение к их способности к дифференцировке в различные клеточные линии МСК обладают иммуносупрессивными свойствами [18,19], секретируя большое число растворимых факторов, таких как индолеамин-2,3-диоксеназа (IDO), простагландин-2, интерлейкин (ИЛ)-10, трансформирующий фактор роста β, оксид азота, HLA-G5, белок-индуцибельный фактор-индуцируемый опухолевым геном 6 (TSG-6), МСК способны ингибировать активацию комплемента, подавлять пролиферацию Т-и В-лимфоцитов, NK-клеток, менять соотношение между различными субпопуляциями Т-клеток, индуцировать пролиферацию регуляторных Т-клеток. Вследствие этого МСК используют для лечения различных заболеваний: болезнь Крона, болезнь Альцгеймера, инфаркт миокарда, сахарный диабет 1-го типа [11,[21][22][23].…”
Section: ââåäåíèåunclassified